2014
DOI: 10.1155/2014/386174
|View full text |Cite
|
Sign up to set email alerts
|

A High‐Performance Control Method of Constant V/f‐Controlled Induction Motor Drives for Electric Vehicles

Abstract: A three-phase induction motor used as a propulsion system for the electric vehicle (EV) is a nonlinear, multi-input multi-output, and strong coupling system. For such a complicated model system with unmeasured and unavoidable disturbances, as well as parameter variations, the conventional vector control method cannot meet the demands of high-performance control. Therefore, a novel control strategy named least squares support vector machines (LSSVM) inverse control is presented in the paper. Invertibility of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…(9)(10)(11)(12) show clearly the effectiveness of the FTC scheme that occurs during the application of the fault by removing all defects thanks to the FTC strategy. In faulty conditions, it is found that the observer has better performance for high and low speeds.…”
Section: Experimental Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…(9)(10)(11)(12) show clearly the effectiveness of the FTC scheme that occurs during the application of the fault by removing all defects thanks to the FTC strategy. In faulty conditions, it is found that the observer has better performance for high and low speeds.…”
Section: Experimental Testsmentioning
confidence: 99%
“…They have received a great attention from the research community. Control methodologies have been actively developed and applied to EVs to improve the EVs performances [10,11]. A classical EV traction system is studied using an induction motor drive.…”
Section: Introductionmentioning
confidence: 99%
“…Induction motors (IMs), the most widely used electrical motors, are renowned for their dependability, affordability, sleek form, and robust construction. Furthermore, because to developments in power electronics and microprocessor technology, high-speed IMs powered by variable frequency provide a number of advantages in terms of durability, little maintenance, low cost, craftwork, and other aspects [1,2]. The specifications for testing synchronous and induction devices are detailed in great depth in [3].…”
Section: Introductionmentioning
confidence: 99%
“…High performance Induction Motor (IM) drives require a fast dynamic response, parameter variation robustness, disturbance rejection capabilities, and simple software and hardware implementation [1], [3]. Field Oriented Control (FOC) [4], Direct Torque Control (DTC) [5], and Model Predictive Control (MPC) [6] are the most commonly used control methods for high performance IM drives [7].…”
Section: Introductionmentioning
confidence: 99%